The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1292/jvms.59.9
|View full text |Cite
|
Sign up to set email alerts
|

A Characteristic of Aspirin-Induced Hearing Loss in Auditory Brainstem Response of Conscious Rats.

Abstract: ABSTRACT. The acute effects of aspirin on auditory functions were examined electrophysiologically in conscious rats with chronically implanted electrodes for auditory brainstem response (ABR) recording. A single intravenous injection of aspirin at a dose of 225 mg/kg caused a reduction in the amplitude of the ABR P1 wave evoked by a 2 kHz tone pip 1 and 24 hr after dosing at almost all sound intensity levels, while the P1 amplitude at 4 kHz was reduced mainly 1 hr after dosing, and the P1 amplitude at 8 kHz wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…These results in the present study indicate that a single injection of aspirin causes impairment of auditory function, i.e., hearing loss, and that in rats the function for low sound frequency is vulnerable to the effects of aspirin and hearing was apparently unaffected by this drug at 4, 8 or 10 kHz of the frequencies using to restrict the variation normally found between threshold intensities and frequencies. Upon hearing loss, the above our results of the subjective examination using the rat operant were highly consistent with those of the objective test, which was reported previously by Kurata et al [22], with the auditory brainstem response (ABR) of the rat. However, there were discrepancies in the changes at 4 kHz between the both studies.…”
Section: 2supporting
confidence: 92%
See 2 more Smart Citations
“…These results in the present study indicate that a single injection of aspirin causes impairment of auditory function, i.e., hearing loss, and that in rats the function for low sound frequency is vulnerable to the effects of aspirin and hearing was apparently unaffected by this drug at 4, 8 or 10 kHz of the frequencies using to restrict the variation normally found between threshold intensities and frequencies. Upon hearing loss, the above our results of the subjective examination using the rat operant were highly consistent with those of the objective test, which was reported previously by Kurata et al [22], with the auditory brainstem response (ABR) of the rat. However, there were discrepancies in the changes at 4 kHz between the both studies.…”
Section: 2supporting
confidence: 92%
“…Myers and Bernstein [27] reported that the hearing impairment induced by aspirin and salicylates in human does not depend on the sound frequency, but others have claimed that higher frequency is more susceptible to the effects of these drugs in human and/or guinea pigs [8,11,23]. Contrary to this, we recently reported that the hearing for lower frequency is more susceptible in the rat [22]. Most reports do agree that hearing loss and/or tinnitus are caused by aspirin; however, Boettcher and Salvi [2] reported that the results on the effects of aspirin on frequency selectivity are conflicting.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…While there is a paucity of data regarding ABR tone intensity function shifts or threshold changes immediately following SS-induced hearing loss and tinnitus, considerable research has been performed examining post-SS threshold shifts within specific auditory structures. An earlier study determining threshold changes based on the ABR peak 1 (P1) amplitude found an increase of approximately 12–20 dB SPL (dependent of stimulus frequency) following aspirin administration in rats [ 23 ]. When the compound action potential (CAP), an assessment of cochlear sensitivity, was measured in rats before and after systemic SS treatment, a significant increase in the thresholds at all tested frequencies was observed along with a significant reduction in CAP response amplitude, although the amplitude reduction was least at 16 kHz [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aspirin is known to induce temporary and reversible thresholds shifts [65]. However, such alterations have been reported for high doses-intravenous injections of 225 mg/kg aspirin or intraperitoneal injections of 300 mg/kg salicylate [66,67]. In our experimental conditions, aspirin alone, supplied at a dose of 10 or 100 mg/kg/day (for comparison, the analgesic dose of aspirin for rats is 100 mg/kg every 4 h) had no toxic effect on hair cells.…”
Section: Discussionmentioning
confidence: 99%